Evaluation of surface properties of modified Ti6Al4V alloy with copper nanoparticles organic nanostructure for biomedical applications: dependency on anticorrosive, antibacterial, and biocompatibility - Altinsoy, Sakir; Erkan, Selen; Ullen, Nuray Bekoz; Ates, Sezen Canim; Evcil, Nese (WALTER DE GRUYTER GMBH, 2025)
In this study, a novel multifunctional copper nanoparticle CuNPs in the organic biomatrix was coated to the surface of Ti6Al4V to create multifunctional features. The synthesis of CuNPs was carried out by plant-mediated green synthesis method obtained from Moringa leaf extract, and the prepared CuNPs were coated on the substrate surfaces as single and double layers with drop casting methods. Characterizations of the synthesized CuNPs were performed by UV-Vis, FTIR, XRD, and SEM methods. Characterization of the modified Ti6Al4V alloy surfaces was performed using SEM-EDS and surface roughness analysis. The electrochemical corrosion, antibacterial behavior, and cytotoxic effects of coated and noncoated Ti6Al4V as a function of biocompatibility properties were also tested. The synthesized CuNPs have a homogeneously dispersed spherical shape. Biocorrosion tests have clearly demonstrated that the coating forms a protective film on the substrate surface, and the resistance increased by 49 %. Antibacterial results show that the single and double-coated Ti6Al4V alloy samples with CuNPs organic nanostructure had improved biocompatibility. However, it was determined that the cytotoxic effect increases proportionally with the coating. The obtained results show the importance of surface modification in the appropriate nanostructure to obtain multifunctional nanoplatforms that show promise in biomedical applications.
Keywords: Ti6Al4V; nanoparticles; biocorrosion; antibacterial; biocompatibility; GREEN SYNTHESIS; ELECTROCHEMICAL CORROSION; OSTEOGENIC ACTIVITY; CUO NANOPARTICLES; STAINLESS-STEEL; TITANIUM; SILVER; COATINGS; RESISTANCE; TI-6AL-4V; Electrochemistry; Metallurgy & Metallurgical Engineering; Materials Science